Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To determine how many roots the polynomial [tex]\( f(x) = \left(x^2 - 1\right)(x + 2)(x - 1)^2 \)[/tex] has, we need to analyze the factors of the polynomial and find the roots.
1. Factor Analysis:
- [tex]\( x^2 - 1 \)[/tex] can be factored as [tex]\( (x - 1)(x + 1) \)[/tex].
- [tex]\( x + 2 \)[/tex] remains unchanged.
- [tex]\( (x - 1)^2 \)[/tex].
So, the polynomial can be written as:
[tex]\[ f(x) = (x - 1)(x + 1)(x + 2)(x - 1)^2 \][/tex]
2. Finding the Roots:
- Set each factor equal to zero and solve for [tex]\( x \)[/tex].
[tex]\[ x - 1 = 0 \Rightarrow x = 1 \][/tex]
[tex]\( x = 1 \)[/tex] appears from both [tex]\( (x - 1) \)[/tex] and [tex]\( (x - 1)^2 \)[/tex], so it has a multiplicity.
[tex]\[ x + 1 = 0 \Rightarrow x = -1 \][/tex]
[tex]\[ x + 2 = 0 \Rightarrow x = -2 \][/tex]
[tex]\( (x - 1)^2 = 0 \Rightarrow x = 1 \)[/tex]. This confirms [tex]\( x = 1 \)[/tex] with a multiplicity of 2.
3. Counting the Roots:
- The roots are: [tex]\( 1 \)[/tex] (from [tex]\( (x - 1) \)[/tex] and [tex]\( (x - 1)^2 \)[/tex]), [tex]\( -1 \)[/tex] (from [tex]\( x + 1 \)[/tex]), and [tex]\( -2 \)[/tex] (from [tex]\( x + 2 \)[/tex]).
- The multiplicity of [tex]\( 1 \)[/tex] is 2 due to [tex]\( (x - 1)(x - 1)^2 \)[/tex].
The roots can be listed with their multiplicities:
[tex]\[ x = 1, -1, -2, 1 \][/tex] (counting [tex]\( x = 1 \)[/tex] twice due to multiplicity).
Therefore, the total number of roots, counting multiplicities, is 5.
The correct answer is:
[tex]\[ 5 \][/tex]
1. Factor Analysis:
- [tex]\( x^2 - 1 \)[/tex] can be factored as [tex]\( (x - 1)(x + 1) \)[/tex].
- [tex]\( x + 2 \)[/tex] remains unchanged.
- [tex]\( (x - 1)^2 \)[/tex].
So, the polynomial can be written as:
[tex]\[ f(x) = (x - 1)(x + 1)(x + 2)(x - 1)^2 \][/tex]
2. Finding the Roots:
- Set each factor equal to zero and solve for [tex]\( x \)[/tex].
[tex]\[ x - 1 = 0 \Rightarrow x = 1 \][/tex]
[tex]\( x = 1 \)[/tex] appears from both [tex]\( (x - 1) \)[/tex] and [tex]\( (x - 1)^2 \)[/tex], so it has a multiplicity.
[tex]\[ x + 1 = 0 \Rightarrow x = -1 \][/tex]
[tex]\[ x + 2 = 0 \Rightarrow x = -2 \][/tex]
[tex]\( (x - 1)^2 = 0 \Rightarrow x = 1 \)[/tex]. This confirms [tex]\( x = 1 \)[/tex] with a multiplicity of 2.
3. Counting the Roots:
- The roots are: [tex]\( 1 \)[/tex] (from [tex]\( (x - 1) \)[/tex] and [tex]\( (x - 1)^2 \)[/tex]), [tex]\( -1 \)[/tex] (from [tex]\( x + 1 \)[/tex]), and [tex]\( -2 \)[/tex] (from [tex]\( x + 2 \)[/tex]).
- The multiplicity of [tex]\( 1 \)[/tex] is 2 due to [tex]\( (x - 1)(x - 1)^2 \)[/tex].
The roots can be listed with their multiplicities:
[tex]\[ x = 1, -1, -2, 1 \][/tex] (counting [tex]\( x = 1 \)[/tex] twice due to multiplicity).
Therefore, the total number of roots, counting multiplicities, is 5.
The correct answer is:
[tex]\[ 5 \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.